The Role of Guidance Teachers in Increasing Students' Self-Confidence at MIS Weigh Opponents - Araudha, Nadra; Mahrani, Khairika; Tu'syadiah, Nurhalimah; Safrina, Tata Rizki; Wahyuni, Sri (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Students who do not have confidence in expressing their opinions, do not dare to ask questions when they do not understand the subject matter are characteristics of low self-confidence. This is due to shyness, hesitation, and feelings of insecure seeing friends who have high self-confidence. The purpose of this study is to analyze the role of counseling teachers in increasing students' self-confidence and identify the factors that cause low self-confidence in students at MIS Timbang Lawan. This research uses a qualitative approach with descriptive methods with information collection techniques using observation, documentation and interviews. Participants in this study were 1 counseling teacher at MIS Timbang Lawan and 5 students. The results of the analysis found, where the counseling teacher helped students in identifying strengths, developing a goal plan and increasing student self-awareness at MIS Timbang Lawan. With emotional support and strategic guidance, counseling teachers help students overcome difficulties, improve academic achievement and achieve life goals. The implications are expected to create a positive and inclusive learning environment that supports student development so that students at MIS Timbang Lawan can increase self-confidence in themselves.